Older adult abuse in a service for sexual and domestic violence: Medico-legal implications from the experience of an Italian center. (September 2022) - Franceschetti, Lorenzo; Merelli, Vera Gloria; Margherita, Manuela; Maggioni, Lidia; Barbara, Giussy; Kustermann, Alessandra; Cattaneo, Cristina
Abstract: Older adults are subject to vulnerability and abusive behaviors have serious negative health consequences. Since the phenomenon is underestimated, several challenges are faced to prevent, diagnose, and treat abuses on older adults. In this context, clinical forensic medicine practitioners can play a pivotal role. A retrospective monocentric analysis of all the files concerning victims of violence observed in the SVSeD Center in Milan over the age of 65 for a five-year period was performed. For each medical report, data regarding the variables of the victims, the type of violence, and the variables of the perpetrators were analysed. Older adult victims of abuses were 166. Abuses against women were more frequent than against men (less than 6 % of consultations). In one third of cases, subjects also suffered from disabling diseases and reported signs of physical violence. Perpetrators were male known individuals in almost 90 % of cases. Violence was perpetrated by a partner or a family member. The present study may help in identifying risk factors for domestic violence against older adults. Consequently, preventive policies should be designed to interrupt the vicious circle of violence. Older adult abuse deserves additional focus and better education for healthcare professionals and further research should be carried out to better understand the actual epidemiology of the phenomenon and to develop therapeutical and caring strategies. Highlights: Older abuse is a serious issue in clinical forensic medicine. Few studies address the theme of medico-legal implications of the phenomenon. The number of cases increased among victims over the considered 5-years-period. Clinical forensic practitioners play a pivotal role in assessing older abuses. Identified risk factors proved the relevance of anti-violence preventive measures.